Pendampingan Rumah Bermain Karakter Untuk Mengurangi Ketergantungan Gadget Anak Kampung Cigablongan - Momon, Momon; Ratnasih, Teti; Nursihah, Arif; Ulfah, Aulia Hermawati; Prasetiawati, Nadia (UIN Sultan Maulana Hasanudin Banten, 2026)
This study aims to reduce gadget dependence through a Character Playhouse accompaniment program that integrates role-playing and storytelling activities as interactive and enjoyable educational alternatives. Experiential learning methods and participatory approaches were applied by facilitators to create a positive and inclusive learning environment Kampung Cigablongan, Desa Mandala, Kecamatan Cimenyan.. The results showed a significant decrease in the duration of gadget use, increased children’s interest in play activities, and the emergence of positive character values such as honesty, responsibility, empathy, and cooperation. This study reinforces the role of the Character Playhouse as an effective medium to divert children’s attention from gadgets while holistically supporting character development. Recommendations are provided to optimize the roles of parents, educators, and community members in managing children's gadget use and in developing sustainable character education programs.